One-Year Survival And Performance Status In Adult Patients With Sepsis, Severe Sepsis, And Septic Shock - Alkhalaf, Mustafa Salman M. (2013)
Sepsis, based on a number of researches, is considered a significant cause of morbidity and mortality. Recognition of long-term sequelae in survivors from critical illnesses has shifted the outcome values from reduction in hospital mortality to ‘patient centered outcomes’, such as health related quality of life (HR-QOL). There is limited data available on long-term follow-up survivors with severe sepsis and septic shock (SS & SK). Therefore, the objectives of this study were to determine who were able to survive versus those unable to survive for one-year post-hospital discharge and to ascertain their performance status, survival versus time post discharge and prognostic factors. A retrospective cohort and cross-sectional study was conducted in relation to adult patients (≥18 years) who were admitted to the medical-surgical and trauma ICU of a tertiary care hospital, at least 24 hours during the period between April 2007 and March 2010. The patients selected were the ones who were still alive at the time of hospital discharge. Survivors were interviewed on the telephone to determine their performance status after one-year of their hospital discharge using “Karnofsky performance status scale”.